Studi Kebutuhan Fasilitas untuk Perancangan Pusat Pelatihan Atlet Bela Diri di Surabaya - Narendra Raffee Riady; Mufidah Mufidah; Tigor Wilfritz Soaduon Panjaitan (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Martial arts training centers are essential facilities that support the technical, physical, and mental development of athletes. This study aims to identify the facility requirements and architectural design criteria for martial arts training centers in Surabaya. A qualitative descriptive method was employed, utilizing literature reviews, field observations, and interviews with relevant stakeholders. The findings indicate that the required facilities include a main training area, supporting spaces, and operational support facilities, all of which must be designed in accordance with the specific characteristics of each martial art discipline. Furthermore, the implementation of appropriate zoning systems and design criteria—such as flexibility, safety, comfort, and functional integration—plays a significant role in enhancing the effectiveness of the training environment. Properly designed facilities not only accommodate diverse training needs but also contribute to optimizing athlete performance. Therefore, a comprehensive architectural approach is necessary to ensure that martial arts training centers can function efficiently and sustainably in supporting long-term athlete development.